2007
DOI: 10.4049/jimmunol.179.4.2368
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Persistence of Codominant Human CD8+ T Cell Clonotypes Is Not Limited by Replicative Senescence or Functional Alteration

Abstract: T cell responses to viral epitopes are often composed of a small number of codominant clonotypes. In this study, we show that tumor Ag-specific T cells can behave similarly. In a melanoma patient with a long lasting HLA-A2/NY-ESO-1-specific T cell response, reaching 10% of circulating CD8 T cells, we identified nine codominant clonotypes characterized by individual TCRs. These clonotypes made up almost the entire pool of highly differentiated effector cells, but only a fraction of the small pool of less differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 55 publications
6
42
0
Order By: Relevance
“…22 Following multiple booster vaccinations, T-cell responses were maintained at high levels over extended periods of time, confirming previous data on cancer-specific human CD8 Tcells. 35,36 The functionality on a per T-cell basis was increased in patients with high T-cell frequencies, as observed previously in mice and humans. 35,37 Moreover, high frequency T-cell populations exhibited high proportions of CD28 neg cells, which showed enhanced effector function as compared to CD28 pos cells (the latter including memory cells), indicating that CD28 neg populations are enriched for effector cells.…”
Section: Tumor Immunologysupporting
confidence: 65%
See 1 more Smart Citation
“…22 Following multiple booster vaccinations, T-cell responses were maintained at high levels over extended periods of time, confirming previous data on cancer-specific human CD8 Tcells. 35,36 The functionality on a per T-cell basis was increased in patients with high T-cell frequencies, as observed previously in mice and humans. 35,37 Moreover, high frequency T-cell populations exhibited high proportions of CD28 neg cells, which showed enhanced effector function as compared to CD28 pos cells (the latter including memory cells), indicating that CD28 neg populations are enriched for effector cells.…”
Section: Tumor Immunologysupporting
confidence: 65%
“…Thus, strong T-cell responses dominated by advanced differentiated CD28 neg T-cells may be highly functional and can persist over many years. 35,36 It has been suggested that increased incidence of infection and cancer of elderly individuals may be related to functional T-cell deficiencies. 24 A recent mouse study indicated that the appropriate choice of state-of-the-art vaccine adjuvants may overcome such deficits.…”
Section: Tumor Immunologymentioning
confidence: 99%
“…In particular, because of its frequent expression in tumors and immunogenicity in advanced cancer patients, NY-ESO-1 is currently viewed as an ideal candidate for thera-peutic tumor antigen-based vaccines. Recently, we reported an unusually strong natural tumor-specific immune response against NY-ESO-1 157-165 in patient LAU 50 with advanced melanoma (11), characterized by expansions of codominant T cell clonotypes bearing distinct BV1, BV8, or BV13 TCRs (12). These data prompted us to examine the proportion of BV1, BV8, and BV13 TCRs present within NY-ESO-1-specific T cells of peptide-stimulated PBMCs from four additional melanoma patients with naturally occurring NY-ESO-1-specific CTL responses (13).…”
Section: Naturally Occurring Ny-eso-1157-165-specific Cd8 ؉ T Cell Rementioning
confidence: 99%
“…Using an approach that combines flow cytometry based-cell sorting, TCR spectratyping, and sequencing at the single cell level, we recently identified, in a single patient (LAU 50), nine codominant NY-ESO-1-specific T cell clonotypes characterized by distinct BV1, BV8, or BV13 TCRs sequences (12). Extensive studies of their clonal composition revealed a high degree of sequence homology of the NY-ESO-1-specific TCRs bearing the TCR BV8 gene segment (Fig.…”
Section: Naturally Occurring Ny-eso-1157-165-specific Cd8 ؉ T Cell Rementioning
confidence: 99%
See 1 more Smart Citation